THE INFLUENCE OF NEEDS AND TRUST FACTORS ON INDEBTED BEHAVIOUR AT ABDURRAB'S ISLAMIC BAITUL MAAL WAT TAMWIL - idel waldelmi; Afvan Aquino (Inovbiz: Jurnal Inovasi Bisnis, 2021)
Based on the results of the research that has been carried out, it is found that the Trust Factor is the main basis of a sharia financial institution and this can be seen from the data that the level of trust of members of the BMT / Islamic Islamic Cooperative Abdurrab is very high in this financial institution. BMT Members Applying for financing / debt / borrowing is not for the lifestyle of BMT Syariah members, where the purpose of BMTIA members to borrow / borrow is none other than to meet the needs needed for daily needs. Factor needs that arise from BMT members, namely the need to feel safer, according to sharia, halal and reassuring, this is the reason why people prefer to join sharia financial institutions / BMTs and for additional business capital needs. Based on the results of multiple linear regression, previously the data were tested for validity, reliability and normality test in information processing that the magnitude of the influence of the need factor and the trust factor on BMT. The research was carried out at BMT Islam Abdurrab, to members of the BMT. The method used in this research is quantitative